Globalization and Multiculturalism : Text is published in periodical "Survey" 1-2, 2006 - Repovac, Hidajet (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
Is it today possible at all to have a realistic and critical approach to reality, or is it possible to transcend the prevailing conformism and the avalanche of the political phrase and kitsch to reach the level of intellect worthy of the 21st century? Is there a sentiment that overcomes the crisis and that can introduce us to a new practice, completely different from the one we, unfortunately, were the witnesses of in the last decade of the second millennium? Or, perhaps, this question that has been asked for thousands of times through history is completely superfluous since it failed to draw any serious and permanent moral.